2019
DOI: 10.1101/532705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnosed and undiagnosed Diabetes mellitus among urban adults: a population based cross-sectional study

Abstract: Background: Globally, diabetes mellitus (DM) accounts for 8.8% (424.9 million) morbidity and 4 million deaths. In 2017, more than 79% of people with diabetes live in low-and middle-income countries. To this end, locally available evidence can identify target groups for intervention.However, in resource-poor settings, population-based evidence on diabetes prevalence and on its risk factors is lacking. This study, therefore, assessed prevalence of Diabetes mellitus and associated factors among adults living in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
2
4
1
Order By: Relevance
“…This finding is comparable with findings of studies done in Indonesia (3.5%), 28 Northwest Nigeria (4.3%), 29 Gilgel Gibe Field Research Center, Ethiopia (3.8%), 30 and Dire Dawa town (3.3%). 31 However, the current study found a relatively higher proportion of unrecognized DM than the study conducted in Kenya (2.4%), 16 Benin (1.4%), 32 Southern Ethiopia, Sidama zone (1.9%), 33 and rural Koladiba town (2.3%). 34 This discrepancy might be due to differences in socio-demographic characteristics of study participants, study setting, and sample size.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This finding is comparable with findings of studies done in Indonesia (3.5%), 28 Northwest Nigeria (4.3%), 29 Gilgel Gibe Field Research Center, Ethiopia (3.8%), 30 and Dire Dawa town (3.3%). 31 However, the current study found a relatively higher proportion of unrecognized DM than the study conducted in Kenya (2.4%), 16 Benin (1.4%), 32 Southern Ethiopia, Sidama zone (1.9%), 33 and rural Koladiba town (2.3%). 34 This discrepancy might be due to differences in socio-demographic characteristics of study participants, study setting, and sample size.…”
Section: Discussioncontrasting
confidence: 85%
“…This is in line with previous studies conducted around the world. 16,17,31,37,[46][47][48] This is most likely due to a decline in lean body mass and an increase in body fat, particularly visceral adiposity which may contribute to the development of insulin resistance, the tendency of low physical activity, and increased body weight. 44,49 This also supplemented with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16]31 Moreover, the result is higher than other similar studies conducted in Ethiopia, namely in Mizan Aman (6.5%), Dire Dawa city (8.95%), Gilgel Gibe of Jimma zone (4.4%), in Addis Abeba (5%) and at Bishoftu town (5%). 7,17,[19][20][21][22] In the same way our result is much higher than prevalence of type 2 diabetes in other Sub-Saharan countries like 0.6% in rural Uganda, a study based on random plasma glucose test 34 and 0.8% in rural Cameroon, a study based on fasting blood glucose test/oral glucose tolerance test. 35 This variation may be due to variances in the period the studies were done, the area of the study, designs of the study, sample sizes used, the sociodemographic and life style of the studied population and the composition of the study population.…”
Section: Discussionsupporting
confidence: 49%
“…3 Preceding studies through the World stated the diabetes mellitus prevalence ranges from 1.4% to 13.55%. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Some of the factors associated with the incidence of diabetes encompassed: being overweight and obese, 7,[21][22][23][24]27,28,32 older age, 17,18,21,31,32 having tertiary educational level, 18,21 poor physical activity, 31 having a family history of DM, 21,22,29 low fruit and vegetable consumption, 17 cigarette smoking, 7,31 alcohol consumption 15,22 waist to hip ratio (WHR), 7,18,21,22,24,…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the prevalence of T2DM was found to be higher when compared to national [8,18] as well as other small-scale studies [12,[19][20][21][22][23][24][25] conducted so far in Ethiopia. This could be due to different reasons.…”
Section: Discussionmentioning
confidence: 50%